Prevalence of therapeutic use exemptions at the Olympic Games and association with medals: an analysis of data from 2010 to 2018 - Vernec, A.; Healy, D. (British Journal of Sports Medicine, 2020)
Objectives The percentage of athletes with Therapeutic Use Exemptions (TUEs) competing in elite sport and the association with winning medals has been a matter of speculation in the absence of validated competitor numbers. We used International Olympic Committee (IOC) and World Anti-Doping Agency (WADA) data to identify athletes competing with TUEs at five Olympic Games (Games) and a possible association between having a TUE and winning an Olympic medal.